2018
DOI: 10.3847/1538-4357/aaf797
|View full text |Cite
|
Sign up to set email alerts
|

Vortex Flows in the Solar Atmosphere: Automated Identification and Statistical Analysis

Abstract: Aims. Due to the fundamental importance of vortices on the photosphere, in this work we aim to fully automate the process of intensity vortex identification to facilitate a more robust statistical analysis of their properties. Methods. Using on-disk observational data of the Fe i continuum, the process of vortex identification is fully automated, for the first time in solar physics, with the help of an established method from hydrodynamics initially employed for the study of eddies in turbulent flows (Graftiea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(49 citation statements)
references
References 37 publications
3
43
1
2
Order By: Relevance
“…Vortical flows in the photosphere have been investigated using velocity fields derived from both observations (Bonet et al 2010;Attie et al 2009;Bonet et al 2008;Balmaceda et al 2010;Giagkiozis et al 2018;Requerey et al 2018;Tziotziou et al 2018Tziotziou et al , 2019Shetye et al 2019) and magnetohydrodynamics (MHD) simulations (see e.g. Kitiashvili et al 2012b;Moll et al 2012;Wedemeyer-Böhm et al 2012;Wedemeyer & Steiner 2014;Kato & Wedemeyer 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Vortical flows in the photosphere have been investigated using velocity fields derived from both observations (Bonet et al 2010;Attie et al 2009;Bonet et al 2008;Balmaceda et al 2010;Giagkiozis et al 2018;Requerey et al 2018;Tziotziou et al 2018Tziotziou et al , 2019Shetye et al 2019) and magnetohydrodynamics (MHD) simulations (see e.g. Kitiashvili et al 2012b;Moll et al 2012;Wedemeyer-Böhm et al 2012;Wedemeyer & Steiner 2014;Kato & Wedemeyer 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The conservation of angular momentum forces the plasma to rotate around the center of the downdraft, generating small-scale vortexes. These vortexes have been extensively detected in observations of the photosphere (Brandt et al, 1988;Simon and Weiss, 1997;Attie et al, 2009;Bonet et al, 2010;Balmaceda et al, 2010;Vargas Domínguez et al, 2011) and also have been observed in the quiet Sun chromosphere as a signature of plasma moving along curly magnetic field lines in coronal holes (Wedemeyer-Böhm and Rouppe van der Voort, 2009). Simulations indicate that the vortexes occurring in strongly magnetized regions are closely connected with dissipation processes providing localized heating in the lower parts of the solar atmosphere (Moll et al, 2012), and observations usually associate vortex detection with bright points (Bonet et al, 2008).…”
Section: Introductionmentioning
confidence: 88%
“…Unfortunately, there are some issues regarding the LCT-FLCT method. As pointed by Démoulin and Berger (2003), if the flux tube is inclined when it rises through the solar atmosphere, the point where it crosses the photosphere moves horizontally. This apparent motion can be interpreted by the LCT-FLCT method as a proper horizontal motion, and Démoulin and Berger (2003) suggested a correction if the tangential component of the magnetic field and the vertical component of the velocity are known.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations